Psikologi Subjek Didik Dalam Pandangan Ibnu Sina - Hadini Hadini (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2013)
Understanding of child psychology course is a theme that is vital for an educational institution if he wants to achieve the ultimate goal of education. Without a deep understanding of these aspects will be able to make his way education becomes useless, or even can be fatal to a child's life. Because errors in the view of the subsidiary, it would be also wrong in the design or the design of learning, if the design is not in accordance with the spirit of education children of the educational process will be in vain. Currently it has a lot of studies about child psychology, but generally many of the studies referred to the West, while it is known that the empirical epistemology Western scientific, rationalist and positivist certainly be questioned. Therefore there is no other way but to be re-referred to the scientists were able to cover the gap of western methodology. In this case the name of Ibn Sina seems appropriate to refer to his thinking, which is due to its ability to successfully combine empirical dimension to the method of intuition. From search results found thoughts about the importance of child psychology, such as thinking about talent, and various inclinations such as the tendency of imitation, play and tendency to compete. Study of Ibn Sina that have for centuries turned out to be legitimized by modern studies of Educational Psychology at the moment. Pemahaman tentang psikologi anak tentu saja merupakan sebuah tema yang vital bagi sebuah lembaga pendidikan jika ia ingin mencapai sasaran akhir pendidikan. Tanpa pemahaman yang mendalam terhadap aspek ini akan bisa membuat jalannya pendidikan menjadi sia-sia, atau bahkan bisa berakibat fatal bagi kehidupan si anak. Sebab kesalahan dalam melihat entitas anak, maka akan bisa pula salah dalam desain atau dalam rancangan pembelajarannya, jika desain pendidikan tidak sesuai dengan jiwa anak tentu proses pendidikan akan sia-sia. Saat ini memang telah banyak kajian-kajian psikologi tentang anak, namun umumnya banyak dirujuk dari kajian Barat, padahal diketahui bahwa epistemologi keilmuan Barat yang empiris, rasianalis dan positivis tentu saja harus dipertanyakan. Karenanya tidak ada jalan lain kecuali harus kembali merujuk pada ilmuan yang bisa menutupi kesenjangan metodologi Barat. Dalam hal ini nama Ibnu Sina dipandang tepat untuk dirujuk pemikirannya, ini karena kemampuannya yang berhasil mengkombinasikan dimensi empiris dengan metode intuisi. Dari hasil penelusuran didapati pemikiran-pemikiran pentingnya tentang psikologi anak, seperti pemikirannya tentang bakat, dan berbagai kecenderungan-kecenderungan anak seperti kecenderungan berimitasi, bermain dan kecenderungan untuk berkompetisi. Kajian Ibnu Sina yang telah berabad-abad tersebut ternyata dilegitimasi oleh kajian Psikogi Pendidikan modern saat ini.